2010
DOI: 10.1108/rjta-14-03-2010-b007
|View full text |Cite
|
Sign up to set email alerts
|

Improved Discrimination and Prediction of Drapability of Fabrics

Abstract: A garment is regarded as desirable and beautiful if it covers the body with harmony and gracefulness. High drape, lightweight and soft handle fabrics are in demand, particularly for womenswear garments such as dresses, shirts, skirts, trousers and suits. Fabric drapability can be measured by a number of drapemeters for different modes of drapability such as static, dynamic and revolving. It has been shown that the drape coefficients, Ds , Dd and Dr , associated with these respective modes of drapability can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…As the coefficient of variation CV% was used to measure the drape coefficient's dispersion within a group of fabrics. The higher the CV% was, the higher the sensitivity to differentiate between fabrics within one group.I ,I , I showed significantly higher CV% values than the relative D , D and D which indicated that these new parameters significantly distinguished between different fabrics [83].…”
Section: Dynamic Drape Parametersmentioning
confidence: 93%
See 3 more Smart Citations
“…As the coefficient of variation CV% was used to measure the drape coefficient's dispersion within a group of fabrics. The higher the CV% was, the higher the sensitivity to differentiate between fabrics within one group.I ,I , I showed significantly higher CV% values than the relative D , D and D which indicated that these new parameters significantly distinguished between different fabrics [83].…”
Section: Dynamic Drape Parametersmentioning
confidence: 93%
“…This means that wool fabrics with high drapeability could be engineered using suitable production parameters for the fabric starting with the fibre content through the yarn to the fabric structure and mechanical properties endowed by the finishing process. This would be useful information for researchers working on engineering fabrics for certain purposes (fit for purpose), as they are able to engineer fabrics with high drapeability using the existing knowledge and rules with respect to the selection of fibre, yarn, fabric and finishing production and process criteria (see Table 3.1Table 4.1) [83]. …”
Section: Controlling Drape Behaviour Of Fabricmentioning
confidence: 99%
See 2 more Smart Citations
“…Air permeability is an important factor in the comfort of a fabric as it plays a role in transporting moisture vapor from the skin to the outside atmosphere. The assumption is that vapor travels mainly through fabric spaces by diffusion in air from one side of the fabric to the other [9]. Air permeability was measured via standard norm ISO 9237, it is defined as the volume of air in liters which is passed through 10 cm² of the fabric in one minute at a pressure of 500 Pa. Due to the way which yarns, and fabrics are constructed, a large proportion of the total volume occupied by a fabric is usually airspace.…”
Section: Elaboration Of a Conductive Textile By Coating For Clothes Ementioning
confidence: 99%